Probabilistic Genotyping of Microhaplotype Data, 1993-2003 - Podini, Daniele ([Verlag nicht ermittelbar], 2023)
Microhaplotypes (MHs) are an emerging forensic DNA marker characterized by sets of single nucleotide polymorphisms (SNPs) within a short distance of each other displaying multiple allelic combinations. Although less polymorphic than short tandem repeat polymorphisms (STRs), they have some advantages, such as alleles all of the same size within a locus, absence of stutter artifacts, and lower mutation rates than that of STRs. Several MH-multiplex panels have been reported in the past, including the 74-locus panel developed in the research team's laboratory. Casework implementation of such large panels is only feasible if paired with probabilistic genotyping (PG) as manual deconvolution of complex mixtures would be excessively time consuming and not compatible with conventional forensic DNA laboratory operations. In this study, DNA-View Mixture Solution and EuroForMix PG software were adapted to processing MH data from 74 loci analyzed on the Ion S5 massively parallel sequencing (MPS) platform. Relative fluorescence unit (RFU) values were replaced by allele-sequence coverage and tested on a set of DNA mixtures. The goals of this project were to (1) adapt and thoroughly test the two PG software platforms for the use multiplex MH data for DNA mixture interpretation, and (2) generate a data repository of mixtures and references that can be used by developers and users to adapt other PG software to intake MH data. The data are organized into spreadsheet type files. Data consists of likelihood ratios (Log10LR) of possible hypotheses involving mixture samples. Log10LRs are averaged across samples and categorized across 4 population frequencies: African American, European, Asian American, and Southwest Hispanic.